2013
DOI: 10.1073/pnas.1301889110
|View full text |Cite
|
Sign up to set email alerts
|

Colony-forming cells in the adult mouse pancreas are expandable in Matrigel and form endocrine/acinar colonies in laminin hydrogel

Abstract: The study of hematopoietic colony-forming units using semisolid culture media has greatly advanced the knowledge of hematopoiesis. Here we report that similar methods can be used to study pancreatic colony-forming units. We have developed two pancreatic colony assays that enable quantitative and functional analyses of progenitor-like cells isolated from dissociated adult (2-4 mo old) murine pancreas. We find that a methylcellulose-based semisolid medium containing Matrigel allows growth of duct-like "Ring/ Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
183
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(204 citation statements)
references
References 57 publications
20
183
1
Order By: Relevance
“…One recent study, which used in vitro semisolid medium culture, showed that Sox9 + CD133 + pancreatic ductal cells from adult mice are able to give rise to three cell lineages, including insulin-producing β cells, ductal epithelial cells, and acinar cells (23,24). These results indicate that Sox9 + CD133 + pancreatic ductal cells from adult mice have the potential to differentiate into insulin-producing β cells in culture, if induced by specific conditions.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…One recent study, which used in vitro semisolid medium culture, showed that Sox9 + CD133 + pancreatic ductal cells from adult mice are able to give rise to three cell lineages, including insulin-producing β cells, ductal epithelial cells, and acinar cells (23,24). These results indicate that Sox9 + CD133 + pancreatic ductal cells from adult mice have the potential to differentiate into insulin-producing β cells in culture, if induced by specific conditions.…”
mentioning
confidence: 68%
“…Medium hyperglycemia induced the presence of Sox9/EGFP + Ins + cells among ductal epithelial cells, and GE treatment increased the frequencies of the Sox9/EGFP + Ins + cells. A recent study reported that Sox9 + CD133 + cells contained β-cell progenitors (23), and multipotent progenitors in the pancreas of mice and human could be Insulin + (28). Whether or not these Sox9 + Ins + ductal cells are progenitors or "hybrid" cells mentioned above remains unclear, and it is under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, tri-lineage potential was demonstrated for adult centroacinar cells (enriched by high aldehyde dehydrogenase 1 enzymatic activity) [19] and adult ductal cells (enriched by CD133 and Sox9 co-expression) [20]. These cells can be isolated, expanded, and differentiated in vitro into all three pancreatic lineages, which include glucose-responsive b-like cells [19,20].…”
Section: Onward Ngn3mentioning
confidence: 99%
“…Although the existence of adult pancreatic progenitor cells in vivo remains debatable (26)(27)(28)(29), we recently identified rare progenitor cells in the adult pancreas that possess extensive selfrenewal and differentiation capacities in vitro (30). These adult progenitor cells, which are CD133 + Sox9 + , are enriched in the ductal cell fraction and can activate Pdx1 and Ngn3 expression before terminal differentiation into endocrine-like cells (30).…”
mentioning
confidence: 99%
“…These adult progenitor cells, which are CD133 + Sox9 + , are enriched in the ductal cell fraction and can activate Pdx1 and Ngn3 expression before terminal differentiation into endocrine-like cells (30). Whether TETs, TDG, and miRNAs may affect differentiation of pancreatic cell lineages has not been tested.…”
mentioning
confidence: 99%